MuhaffazÃ¢t al-Al’Ã¢b al-Raqmiyyah (Gamification) fÃ® Ta’lÃ®mi al-Lughah al-’Arabiyyah: DirÃ¢satu al-AbhÃ¢ts al-MansyÃ»rah fÃ® TathbÃ®qi MuhaffazÃ¢ti al-Al’Ã¢b al-’Arabiyyah fÃ® IndÃ»nÃ®siyÃ¢ - Ø¹Ø¨Ø¯ Ø§Ù„Ø±ØÙ…Ù† ØØ³ÙŠÙ†, Ø¹Ø¨Ø¯ Ø§Ù„ØÙƒÙŠÙ… (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2024)
Student engagement and motivation are highly necessary to achieve satisfactory learning outcomes. Gamification has been employed as one of the approaches to language learning in recent years with the aim of enhancing student engagement, motivation, and learning outcomes. The aims of this study are to examine the impact of gamification on Arabic language learning and identify the applicable gamification strategies. This study utilizes a literature review where the researcher analyzes research articles on the use of gamification in Arabic language learning and subsequently conducts an analysis of the gamification applications that can be employed in Arabic language learning. The results of the research demonstrate that the use of gamification applications can yield positive impacts, and there are numerous applications that can be utilized in Arabic language learning, both for language skill acquisition and linguistic elements. Furthermore, the result of this research can be the main reference for Arabic language education practitioners.